The Calculus of Finite Differences John Stalker March 15, 2016 Theorem 1 Suppose x1 < x2 < · · · < xm . The following three conditions are equivalent: 1. As formal power series in D, m n−1 X X cj,k D k exp(xj D) = O(D n ), j=1 k=0 2. For any polynomial p of degree less than n, m n−1 X X cj,k p(k) (xj ) = 0. j=1 k=0 3. There is a function r such that if f ∈ C n ([x1 , xm ]) then m n−1 X X cj,k f (k) (xj ) = j=1 k=0 Z xm x1 r(x)f (n) (x) dx. Condition 3 clearly implies Condition 2, since the integrand vanishes if f is a polynomial p of degree less than n. We now show that Conditions 1 and 2 are equivalent. Condition 1 means that m n−1 X X cj,k D k exp(xj D) = 0 j=1 k=0 in the ring R1 of polynomials in D, modulo the ideal generated by D n . Consider the vector space V of polynomials in x of degree less than n. d/dx is an endomorphism of this vector space. Its n’th power is zero, but all lower 1 powers are linearly independent. Let R2 be the ring of endomorphisms generated by d/dx. Then R1 and R2 are isomorphic, the isomorphism taking D to d/dx. Henceforth we identify R1 and R2 via this isomorphism. We therefore drop the subscripts, and write D for d/dx. Having made this identification, m n−1 X X j=1 k=0 cj,k D k exp(xj D)p (x) = m n−1 X X cj,k p(k) (x + xj ). j=1 k=0 Suppose Condition 1 holds. Then m n−1 X X cj,k D k exp(xj D)p = 0 j=1 k=0 for all p, and hence and thus m n−1 X X j=1 k=0 cj,k D k exp(xj D)p (0) = 0 m n−1 X X cj,k p(k) (xj ) = 0. j=1 k=0 Suppose Condition 2 holds. If p is a polynomial of degree less than n then so is q, defined by q(x) = p(x + y) for all y. So m n−1 X X cj,k q (k) (xj ) = 0, j=1 k=0 or m n−1 X X cj,k p(k) (xj + y) = 0. j=1 k=0 In other words, m n−1 X X j=1 k=0 cj,k D k exp(xj D)p (y) = 0 for all y. Thus m n−1 X X cj,k D k exp(xj D)p j=1 k=0 2 is the zero polynomial. But p was an arbitrary element of V , so m n−1 X X cj,k D k exp(xj D) = 0 j=1 k=0 as an endomorphism of V . In other words, Condition 1 holds. It remains to prove that Condition 2 implies Condition 3. This we will prove with the explicit r r(x) = m n−1 X X cj,k bn−k−1 (xj − x) j=1 k=0 where (−z)i /i! if z ≥ 0 0 if z < 0. If i = 0 and z = 0 then we interpret 00 as 1. By Condition 2, bi (z) = m n−1 X X cj,k p(k) (xj ) = 0. j=1 k=0 for all polynomials p of degree less than n. This holds in particular for p(x) = n−1 X l=0 f (l) (x1 ) (x1 − x)l . l! In other words, m n−1 X X n−1 X cj,k j=1 k=0 l=k f (k) (x1 ) (xj − x1 )l−k = 0 (l − k)! or, shifting indices, m n−1 X X n−k−1 X l=1 k=0 i=0 cl,k f (i+k) (x1 ) (xl − x1 )i = 0 i! Now Z xm x1 r(x)f (n) (x) dx = m−1 X Z xj+1 j=1 3 xj r(x)f (n) (x) dx so xm Z x1 r(x)f (n) (x) dx = m−1 m X n−1 XX Z cl,k xj+1 xj j=1 k=0 l=1 bn−k−1 (xl − x)f (n) (x) dx If j ≥ l then the integrand on the right is zero. Otherwise, choose xj < α < β < xj+1 and integrate by parts n − k times, Z β α bn−k−1 (xl − x)f (n) (x) dx = n−k−1 X h bi (xl − α)f (i+k) (α) i=0 i − bi (xl − β)f (i+k) (β) . Taking limits as α tends to xj and β tends to xj+1 , Z xj+1 xj bn−k−1 (xl − x)f (n) (x) dx = n−k−1 X i=0 1h (xj+1 − xl )i f (i+k) (xj+1 ) i! i − (xj − xl )i f (i+k) (xj ) . We then sum over j, m−1 X Z xj+1 xj j=1 bn−k−1 (xl − x)f (n) (x) dx = f (k) (xl ) − n−k−1 X f (i+k) i=0 (x1 − xl )i (x1 ) i! Multiplying by ck,l and summing over k and l, Z xm x1 r(x)f (n) (x) dx = m n−1 X X cj,k f (k) (xj ) j=1 k=0 m n−1 X X n−k−1 X + l=1 k=0 i=0 cl,k (i + k)! (i+k) f (x1 )(xl − x1 )i . i! The second sum is, as we have seen, zero, so Z xm x1 r(x)f (n) (x) dx = m n−1 X X cj,k f (k) (xj ) j=1 k=0 and Condition 3 holds, with r(x) = m n−1 X X cj,k bn−k−1 (xj − x). j=1 k=0 4